Akuntabilitas Kepala Desa Dalam Pembangunan Jalan Di Desa Taja Mulya Kecamatan Betung Kabupaten Banyuasin - VALENTIN, PUPUT; Isabella, Isabella; Amaliatulwalidain, Amaliatulwalidain (Peneliti.net, 2024)
This study uses the theory of accountability from Syahrudin Rasul, there are 5 (five) indicators, namely 1. Honesty and Law 2. Managerial 3. Program 4. Policy 5. Finance. From the results of the research conducted, it was found that the accountability of the village head in road construction in Taja Mulya Village was not effective enough because there were still many damaged roads and also many roads that had not been cast or were still in dirt. The problems in the road construction process are constrained funds for the construction and repair of village roads so that road construction carried out in villages uses more funds from third parties such as the aspirations of the DPRD. The suggestion in this research is that the village government is more concerned with and pays more attention to the condition of village road construction and prioritizes the construction of damaged roads in order to facilitate access to schools and to the gardens where the community works.